2017
DOI: 10.1002/cncr.30568
|View full text |Cite
|
Sign up to set email alerts
|

Lay health educators and print materials for the promotion of colorectal cancer screening among Korean Americans: A randomized comparative effectiveness study

Abstract: Compared with a brochure, LHE outreach yielded greater increases in knowledge but resulted in similar increases in CRC screening in a Korean American population with barriers to health care access. More work is needed to appropriately address logistical and system barriers in this community. Cancer 2017;123:2705-15. © 2017 American Cancer Society.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
35
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 20 publications
(39 citation statements)
references
References 31 publications
(83 reference statements)
3
35
1
Order By: Relevance
“…The most commonly used pedagogic methodologies for training CBHWs were visual aids/flip charts, practice intervention sessions, and role‐playing. A competency assessment measure was described in k = 18 (55%) studies including ongoing supervision throughout intervention period, practice sessions, and a written examination . A form of research skills training including the principle of randomization and the importance of protocol adherence was reported in k = 12 (36%) studies .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The most commonly used pedagogic methodologies for training CBHWs were visual aids/flip charts, practice intervention sessions, and role‐playing. A competency assessment measure was described in k = 18 (55%) studies including ongoing supervision throughout intervention period, practice sessions, and a written examination . A form of research skills training including the principle of randomization and the importance of protocol adherence was reported in k = 12 (36%) studies .…”
Section: Resultsmentioning
confidence: 99%
“…A theory base was explicitly reported (ie, coded yes to item 5 of Theory Coding Scheme) in k = 15 (45%) interventions . Of these 15 studies, a combination of theories was reported in k = 8 (53%) (range 2–4) . The Transtheoretical Model was applied in k = 8 (53%) studies, and the Health Belief Model was reported in k = 7 (47%) studies.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In research, common terms include co‐researchers (Shen et al., ; Vaughn et al., ), lay researchers (Carlisle & Cropper, ; Newell & South, ), peer researchers (Guta et al., ; Logie, James, Tharao, & Loutfy, ) and citizen scientists (Bonney et al., ; Cohn, ; Dickinson, Zuckerberg, & Bonter, ). In education, titles include peer educators (Conner, Gum, Johnson, Cadet, & Brown, ; Nettles & Belton, ), lay educators (Jo et al., ; Mandalia, Stone, Davies, Khunti, & Carey, ) and co‐educators (Coelho, Pooler, & Lloyd, ; Purcell & Wooten, ). In social care, common titles include community health workers, lay health advisors and promotores (Balcazar et al., ; Olsson, Lau, Lifvergren, & Chakhunashvili, ; Perez et al., ; Sun et al., ; Villa‐Torres, Fleming, & Barrington, ).…”
Section: Introductionmentioning
confidence: 99%